Burden of foodborne diseases: think global, act local. (June 2021) - Pires, Sara M; Desta, Binyam N; Mughini-Gras, Lapo; Mmbaga, Blandina T; Fayemi, Olanrewaju E; Salvador, Elsa M; Gobena, Tesfaye; Majowicz, Shannon E; Hald, Tine; Hoejskov, Peter S; Minato, Yuki; Devleesschauwer, Brecht
Highlights: National burden of disease studies are needed to define food safety priorities. Initiatives to support capacity building and collaboration are emerging. Novel methodologies provide opportunities to improve data collection for disease burden estimation in low-resource settings. Abstract : National burden of foodborne disease (FBD) studies are essential to establish food safety as a public health priority, rank diseases, and inform interventions. In recent years, various countries have taken steps to implement them. Despite progress, the current burden of disease landscape remains scattered, and researchers struggle to translate findings to input for policy. We describe the current knowledge base on burden of FBDs, highlight examples of well-established studies, and how results have been used for decision-making. We discuss challenges in estimating burden of FBD in low-resource settings, and the experience and opportunities deriving from a large-scale research project in these settings. Lastly, we highlight the role of international organizations and initiatives in supporting countries to develop capacity and conduct studies.